A influência de decisões arquitetônicas na eficiência energética do Campus vol. 1/UFRN - Lima, Raoni Venâncio dos Santos (2007)
Building design is an effective way to achieve HVAC energy consumption reduction. However, this potentiality is often neglected by architects due to the lack of references to support design decisions. This works intends to propose architectural design guidelines for energy efficiency and thermal performance of Campus/UFRN buildings. These guidelines are based on computer simulations results using the software DesignBuilder. The definition of simulation models has begun with envelope variables, partially done after a field study of thirteen buildings at UFRN/Campus. This field study indicated some basic envelope patterns that were applied in simulation models. Occupation variables were identified with temperature and energy consumption monitoring procedures and a verification of illumination and equipment power, both developed at the Campus/UFRN administration building. Three simulation models were proposed according to different design phases and decisions. The first model represents early design decisions, simulating the combination of different types of geometry with three levels of envelope thermal performance. The second model, still as a part of early design phase, analyses thermal changes between circulation halls lateral and central and office rooms, as well as the heat fluxes and monthly temperatures in each circulation hall. The third model analyses the influence of middle-design and detail design decisions on energy consumption and thermal performance. In this model, different solutions of roofs, shading devices, walls and external colors were simulated. The results of all simulation models suggest a high influence of thermal loads due to the incidence of solar radiation on windows and surfaces, which highlights the importance of window shading devices, office room orientation and absorptance of roof and walls surfaces